Description of the types and content of phase 1 clinical trial consent conversations in practice. (December 2015) - Wall, Louisa; Farmer, Zachary Luke; Webb, Margaret White; Dixon, Margie D; Nooka, Ajay; Pentz, Rebecca D
Background or aims: All agree that informed consent is a process, but past research has focused content analyses on post-consent or on one conversation in the consent series. Our aim was to identify and describe the content of different types of consent conversations. Methods: We conducted a secondary analysis of 38 adult oncology phase 1 consent conversations, which were audio-recorded, transcribed, coded, and qualitatively analyzed for type and content. Results: Four types of consent conversations were identified: (1) priming, (2) patient-centered options, (3) trial centered, and (4) decision made. The analysis provided a robust description of the content discussed in each type of conversation. Two themes, supportive care and prognosis, were rarely mentioned. Four themes clustered in the patient-centered (type 2) conversations: affirmation of honesty, comfort, progression, and offer of supportive care. Conclusion: We identified and described four types of consent conversations. Our novel findings include (1) four different types of conversations with one (priming) not mentioned before and (2) a change of focus from describing the content of one phase 1 consent conversation to describing the content of different types. These in-depth descriptions provide the foundation for future research to determine whether the four types of conversations occur in sequence, thus describing the structure of the consent process and providing the basis for coaching interventions to alert physicians to the appropriate content for each type of conversation. A switch from a focus on one conversation to the types of conversations in the process may better align the consent conversations with the iterative process of shared decision making.